Increased Training Volume Improves Bone Density and Cortical Area in Adolescent Football Players - Varley, Ian; Hughes, David C.; Greeves, Julie P.; Fraser, William D.; Sale, Craig (International Journal of Sports Medicine, 2017)
Habitual football participation has been shown to be osteogenic, although the specific volume of football participation required to cause bone adaptations are not well established. The aim of the present study is to investigate tibial bone adaptations in response to 12 weeks of increased training volume in elite adolescents who are already accustomed to irregular impact training. 99 male adolescent elite footballers participated (age 16±0 y; height 1.76±0.66 m; body mass 70.2±8.3 kg). Tibial scans were performed using peripheral quantitative computed tomography immediately before and 12 weeks after an increase in football training volume. Scans were obtained at 4, 14, 38 and 66% of tibial length. Trabecular density (mg/cm3), cortical density (mg/cm3), cross-sectional area, cortical area (mm2), cortical thickness (mm) and strength strain index (mm3) were assessed. Trabecular (4%) and cortical density (14, 38%), cortical cross-sectional area (14, 38%), total cross-sectional area (66%), cortical thickness (14, 38%) and strength strain index (14, 38%) increased following 12 weeks of augmented volume training (P<0.05). Increased density of trabecular and cortical compartments and cortical thickening were shown following an increased volume of training. These adaptive responses may have been enhanced by the adolescent status of the cohort, supporting the role of early exercise intervention in improving bone strength.
Keywords: bone accrual; irregular impact training; osteogenic exercise; bone strength